Sisters in Crime: Women and illicit sexual affairs in late imperial Chinese erotic fiction - Wai, C (2022)
This research aims to investigate the literary representation of the female relationships and illicit sexual affairs in late imperial China erotic fiction. Focusing on the plots of touqing 偷情 (having secret sexual affairs), this research utilises five selected examples of vernacular erotic fiction composed around 1572-1730 as the main source to investigate women’s lives and social activities in illegal circumstances: Langshi 浪史 (Chronicles of the Libertine), Xiuta yeshi 繡榻野史 (Unofficial History of the Embroidered Couch), Rou putuan 肉蒲團 (The Carnal Prayer Mat), Taohua ying 桃花影 (Shadow of Peach Blossoms), and Dengcao heshang zhuan 燈草和尚傳 (Legend of the Candlewick Monk).